Eco‐balance features and significance of hemihydrate phosphogypsum reprocessing into gypsum binding materials - Gaidučis, Sergejus; Mačiulaitis, Romualdas; Kaminskas, Antanas (Journal of Civil Engineering and Management, 2009)
The classification and grouping of materials investigation according to raw material’s nature and product purpose (use) was conducted by using comparative material energetic usefulness and its production ecobalance analytical methods. Energy expenditures and pollution emissions into the environment were studied and compared to analogical purpose materials. One of the most economically perspective technogenic waste ‐ extractive hemihydrate phosphogypsum was investigated. Two technological production streams of phosphogypsum were studied. It was found, that the energy needs for production of analogical purpose materials (wall partitions) differ significantly. The nature of raw materials has an influence on energetic usefulness. The most effective materials according to their nature, energetic usefulness and environmental protection are mineral ones, especially if they are made with technogenic inorganic waste materials. The best results, from the energetic and ecological point of view, are obtained by using the waste raw material ‐ extractive hemihydrate phosphogypsum. Its reprocessing energy expenditures and pollutant emissions into the environment are several times less, than for other analogical purpose and properties wall materials, also with less environmental pollution. Products made from reprocessing extractive hemihydrate phosphogypsum can replace other energy consuming articles for wall partitions. Santrauka Klasifikuojant ir grupuojant medžiagas pagal žaliavų kilmę ir gaminių paskirtį atlikti lyginamieji medžiagų energinio naudingumo ir jų gamybos ekobalanso analitiniai tyrimai. Nagrinėtos ir lygintos energijos sąnaudos ir teršalų patekimas į aplinką analogiškos paskirties medžiagoms gauti. Tirtos vienos iš perspektyviausių ekonomoniu ir ekologiniu požiūriu technogeninės atliekos – ekstrakcinio pushidračio fosfogipso (E-PG) savybės. Nustatyta, kad energijos poreikis gaminant analogiškos paskirties medžiagas iš esmės skiriasi. Žaliavos kilmė turi įtaką produkcijos energiniam naudingumui. Efektyviausios pagal kilmę energinio naudingumo ir aplinkosaugos požiūriu yra mineralinės medžiagos, ypač jeigu jos pagamintos iš technogeninių neorganinių atliekų. Geriausi rezultatai energiniu ir ekologiniu požiūriu gauti naudojant atliekų žaliavą – E-PG. Jo perdirbimo energijos sąnaudos ir teršalų emisija į aplinką yra kelis kartus mažesnės, negu gaminant kitas analogiškos paskirties ir savybių sienines medžiagas, be to, mažėja aplinkos tarša. Ateityje gaminiai iš perdirbto E-PG galėtų pakeisti pastatų atitvaroms naudojamus keraminius, silikatinius ir kitus energijai imlius dirbinius. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: fosfogipsas, rūgščiosios priemaišos, neutralizuojantys priedai, mechaninė aktyvacija, gipscementis, energinis naudingumas, ekobalansas.